2006
DOI: 10.1113/jphysiol.2006.111310
|View full text |Cite
|
Sign up to set email alerts
|

BDNF increases release probability and the size of a rapidly recycling vesicle pool within rat hippocampal excitatory synapses

Abstract: Exerting its actions pre-, post-and peri-synaptically, brain-derived neurotrophic factor (BDNF) is one of the most potent modulators of hippocampal synaptic function. Here, we examined the effects of BDNF on a rapidly recycling pool (RRP) of vesicles within excitatory synapses. First, we estimated vesicular release in hippocampal cultures by performing FM4-64 imaging in terminals impinging on enhanced green fluorescent protein (eGFP)-labelled dendritic spines -a hallmark of excitatory synapses. Consistent with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
87
2
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(101 citation statements)
references
References 79 publications
(162 reference statements)
11
87
2
1
Order By: Relevance
“…Additional findings that high-frequency stimulation or more natural theta patterns of afferent activity upregulates BDNF expression further corroborate its role in synaptic plasticity (Gooney and Lynch, 2001;Balkowiec and Katz, 2002). Mechanisms underlying the function of BDNF in plasticity include presynaptic (Gottschalk et al, 1998;Pozzo-Miller et al, 1999;Jovanovic et al, 2000;Xu et al, 2000;Zakharenko et al, 2003;Tyler et al, 2006) or postsynaptic actions Lin et al, 1998;Di Luca et al, 2001;Kovalchuk et al, 2002) as well as coordinate pre-and postsynaptic processes (Alder et al, 2005;Gartner et al, 2006). Despite a great deal of progress on the function of BDNF in LTP, investigation of its role in associative learning has only more recently begun to be examined.…”
Section: Introductionmentioning
confidence: 85%
“…Additional findings that high-frequency stimulation or more natural theta patterns of afferent activity upregulates BDNF expression further corroborate its role in synaptic plasticity (Gooney and Lynch, 2001;Balkowiec and Katz, 2002). Mechanisms underlying the function of BDNF in plasticity include presynaptic (Gottschalk et al, 1998;Pozzo-Miller et al, 1999;Jovanovic et al, 2000;Xu et al, 2000;Zakharenko et al, 2003;Tyler et al, 2006) or postsynaptic actions Lin et al, 1998;Di Luca et al, 2001;Kovalchuk et al, 2002) as well as coordinate pre-and postsynaptic processes (Alder et al, 2005;Gartner et al, 2006). Despite a great deal of progress on the function of BDNF in LTP, investigation of its role in associative learning has only more recently begun to be examined.…”
Section: Introductionmentioning
confidence: 85%
“…Studies performed in cultured hippocampal neurons showed that BDNF increases the frequency of miniature excitatory postsynaptic currents, further supporting a presynaptic effect of the neurotrophin (Lessmann and Heumann, 1998;Li et al, 1998;Schinder et al, 2000;Tyler and Pozzo-Miller, 2001). The rapidly recycling pool of synaptic vesicles is targeted by a BDNF-dependent mechanism in the hippocampal CA1 region, and this modulation was shown to be necessary for the enhancement of exocytosis caused by induction of LTP (Tyler et al, 2006). The recycling of synaptic vesicles induced by BDNF requires the presence myosin VI, a minus end-directed actin-based motor, and the adaptor protein GIPC1 [PDZ (postsynaptic density-95/Discs large/zona occludens-1) domain-containing adaptor protein, type 1], which form a complex that can engage TrkB receptors (Yano et al, 2006).…”
Section: Transcription-and Translation-independent Synaptic Regulatiomentioning
confidence: 99%
“…1a-f). The principal dye-labelling step is based on an established approach adopted in a number of previous studies 7,13,33,[38][39][40][41][42] and we outline key strategies to validate its success. Subsequently, detailed methodology for rapid microwave-enhanced fixation 43 and calibrated photoconversion of the target region are provided.…”
Section: Labelling and Visualizing Functional Vesiclesmentioning
confidence: 99%
“…While vesicles appear morphologically equivalent they can be sub-divided into pools on the basis of their functional behaviour, including a recycling pool (see 2,3 , readilyreleasable pool 4 , spontaneous pool 5,6 and superpool 7,8 . Understanding the properties of these pools has become increasingly important with the realization that they are potentially critical substrates in setting synaptic strength 9,10 and represent modifiable targets on which forms of plasticity 9,[11][12][13][14] or disease-like conditions [15][16][17] might act to modulate or disrupt information flow.…”
Section: Introductionmentioning
confidence: 99%